Internationalization–Industrial output nexus: Evidence from 15 late‐industrialized economies. Issue 4 (10th March 2021) - Adeleye, Bosede Ngozi; Sankaran, Arumugam; Jamal, Abdul; K, Arjun
Abstract : The paper empirically examines the internationalization‐output nexus in 15 late‐industrialized countries from 1976 to 2018 using fixed and random effects techniques. The findings reveal that trade openness negatively impacts the industrial output, while the labor force shows a positive and statistically significant impact. Domestic investment and education show negligible and insignificant positive and negative impacts on output, respectively. Investment is supposedly incurring zero marginal productivity of capital as it is high in excess of labor. In a nutshell, it is capital bias. Furthermore, bias in terms of complex skill requirements in production prevents the entry of less‐skilled labor force. Given these outcomes, we conclude that the incremental capital‐output ratio (ICOR) needs to be tested to find out additional intricate issues involved in investment. Besides, the comparative advantage in less skilled labor is underutilized. To overcome this, the policymakers should ensure absorption of such semi‐skilled human capital. This requires removing skill bias and capital bias to a reasonable extent without damaging output generation. Hence, the study suggested that the late‐industrialized nations may use the potential labor force and capital to speed‐up long‐term industrial development by enhancing human capital through training, technical know‐how, etc., to attain sustainable industrial development.